A qualitative descriptive inquiry into factors influencing early weaning and breastfeeding duration among first-time mothers in Papua New Guinea's rural eastern highlands. Issue 1 (February 2022) - Maviso, McKenzie Ken; Ferguson, Bridget; Kaforau, Lillian Maye; Capper, Tanya
Abstract: Background: Exclusive breastfeeding confers multiple maternal and child health benefits. Although breastfeeding initiation following birth is common in Papua New Guinea, many first-time mothers may not achieve optimal breastfeeding duration. Aim: This study aims to explore and describe factors influencing early weaning and breastfeeding duration among first-time mothers in Papua New Guinea's rural eastern highlands. Methods: A qualitative descriptive approach was adopted in this study. Data were collected through semi-structured in-depth interviews with 20 first-time mothers. The interviews transcripts were then thematically analysed. Results: Three key themes identified were: source of breastfeeding information and support; social networks and breastfeeding communication; and balancing perceived gender and maternal roles. The study further identified a lack of fathers' involvement in supporting breastfeeding. Conclusion: Social and relational networks, and maternal factors need to be considered to better understand breastfeeding practices. Efforts to achieve optimal breastfeeding outcomes entail targeted and culturally appropriate programs, including fathers' involvement as they play important roles in breastfeeding and infant feeding practices.